2007
DOI: 10.1016/j.biopha.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and low urinary citrate excretion in calcium stone formers

Abstract: Epidemiological data suggest an association between kidney stones and some features of metabolic syndrome such as an overweight condition, arterial hypertension or glucose intolerance. However, mechanisms remain to be elucidated. This study aimed to evaluate insulin resistance, as assessed by homeostasis model assessment (HOMA-IR), and urine composition analysis in patients affected by calcium nephrolithiasis. A cohort of 61 (38 male, 29-57 years of age) non-diabetic calcium stone formers was studied. Data abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 28 publications
6
65
2
3
Order By: Relevance
“…Several studies have shown an association between metabolic acidosis and diabetes mellitus. In a study of 61 young calcium SFs, Cupisti et al (4) showed an association between insulin resistance and lower urinary citrate excretion. However, our study included an older population of both SFs and NSFs and considered prevalent diabetes rather than measures of insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have shown an association between metabolic acidosis and diabetes mellitus. In a study of 61 young calcium SFs, Cupisti et al (4) showed an association between insulin resistance and lower urinary citrate excretion. However, our study included an older population of both SFs and NSFs and considered prevalent diabetes rather than measures of insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Lower urinary citrate excretion is a known modifiable risk factor for calcium oxalate nephrolithiasis (1,2) and associated with both prevalent hypertension (3) and greater insulin resistance (4). However, the independent associations of several dietary and lifestyle factors and medical conditions with urinary citrate excretion are unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet exposures and physical activity were calculated as updated cumulative average levels as of the baseline (1990) questionnaire. We also summarized intake of cereal fibre and trans fats, glycemic load and the ratio of polyunsaturated to saturated fats (with each component categorized in quintiles and scored 1-5, where 5 was assigned to the healthiest intake) in a diabetes diet score (ranging from [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], with a high diet score associated with a reduced risk of type 2 diabetes mellitus in the Nurses' Health Study. 16 The reproducibility and validity of the food-frequency questionnaires have been described.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…8 In addition, higher levels of serum lactate, a small component of the anion gap, were associated with higher odds of prevalent type 2 diabetes mellitus in the Atherosclerosis Risk in Communities study 9 and with higher odds of incident type 2 diabetes mellitus in a retrospective cohort study of the risk factors for diabetes in Swedish men. 10 Other biomarkers associated with metabolic acidosis, including higher levels of serum ketones, 11 lower urinary citrate excretion 12 and low urine pH, 13 have been associated in crosssectional studies with either insulin resistance or the prevalence of type 2 diabetes mellitus. However, it is unclear whether these associations are a cause or consequence.…”
mentioning
confidence: 99%